Comparative study of visual inspection of the cervix by 3% acetic acid (VIA) versus Pap smear by Bethesda method in sexually active women aged 25-50 years as an equally or more effective cervical cancer screening method in a low resource setup - Saraogi, Mohit Rajendra; Gupta, Alka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the most common cancer in Indian women and is a preventable cancer. Pap smear being an expensive screening test, increased emphasis is being laid on the development of a reliable and cost effective screening method for cervical cancer. This study aims at early detection of cervical dysplastic lesions using a simple and cost-effective screening test like visual inspection of cervix with 3% acetic acid (VIA) and comparing its diagnostic efficacy with the more expensive Pap screening by Bethesda method. Methods: Ours was a prospective study carried out on a 100 sexually active women aged 25-50 years, coming to our OPD. The women were subjected to both a VIA and Pap smear. All Pap and VIA positive women were subjected to a cervical biopsy, whose histopathological report was taken as the gold standard. Results: In our study the sensitivity of VIA was more than that of cytology (100% versus 66.67%) but the specificity was significantly lesser (47.83% compared to the 73.91%). The negative predictive value of VIA was comparable with Pap smear (100% & 85% respectively) as was the positive predictive value (42.86% & 50%). However the diagnostic accuracy of VIA was lower than that of Pap smear (66.67% & 81.25%) in our study. Conclusions: In this study VIA was found to have efficacy comparable to Pap smear in screening cervical cancer. Thus we recommend that VIA could be used as an alternative screening tool to detect early cervical dysplasia - especially in poor resource settings.